Fragmentation as a key driver of tree community dynamics in mixed subtropical evergreen forests in Southern Brazil - Gross A.* (2018)
© 2018 Elsevier B.V.The study of tree community dynamics may help improve our understanding of forest ecosystem function. Here, we aimed to investigate the influences of climate, soils, landscape, forest structure, and chronic anthropogenic disturbances on tree community demography in the fragments of Araucaria Forest in Southern Brazil. Nine forest fragments were inventoried between 2008 and 2012, and were inventoried again from three to six years later. For the tree community in each forest remnant, we calculated mortality, recruitment, basal area loss- and gain, net changes, and turnover rates. For each study area, we also measured altitude, climate, soil type, fragment patch metrics, cattle presence, and tree component structure. We used Principal Component Analyses (PCA) to order the multivariate data (Tree community dynamics: demographic rates; Climate: altitude + climate; Patch metric: area + core + shape + Cai). The relationships between the patterns of the dynamics and the explanatory variables were subjected to regression tree analyses and t tests. We found that the Araucaria Forest dynamics mainly varied in terms of tree mortality and basal area loss rates. In general, mortality and basal area loss rates were smaller within larger fragments, which had a greater proportion of interior areas. Therefore, we concluded that anthropogenic fragmentation is a key driver of tree community dynamics in the Araucaria Forest of Southern Brazil. Based on our results, we would recommend (i) the protection of small and large tracts of forest fragments; and (ii) incentives to promote the silviculture of the most relevant timber species, the light demanding Araucaria angustifolia, in the deforested lands of the region.